The effect of nutrition level on the growth, development and carcass composition of Minnesota no. 1 pigs - Vosloo, W. A.(Willem Adriaan) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc. Agric.) -- University of Stellenbosch, 1958.